The art of PCB reverse engineering : unraveling the beauty of the original design - Tiong, Ng Keng ([Place of publication not identifed] : CreateSpace Independent Publishing Platform, 2015)
This book impart knowledgeon PCBs that relate to the subject of reverse engineering, as a basic understanding of any PCB you intend to reverse engineer is essential to your success.
Before you begin -- Basic preparation work -- Laying out the PCB artwork -- Writig up the schematics -- Advanced topics -- Going from here
PCB reverse engineering :, The
Keywords: PRINTED CIRCUITS -- DESIGN AND CONSTRUCTION